Koordinasi pada Pelayanan Rehabilitasi Sosial Rumah Tidak Layak Huni Kota Surabaya - Adi, Kemala Karisya Aulia; Shobaruddin, M (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
Rehabilitation of uninhabitable houses is one of the services provided by the local government to restore the function of the house by repairing parts of the house. The Social Rehabilitation Program for Uninhabitable Houses in the City of Surabaya (Rutilahu) is critical because settlements are one of the basic human needs essential in increasing human dignity and prosperous quality of life in a just and prosperous society. This study aims to explain coordination in social rehabilitation services for uninhabitable houses in Surabaya. The research method used in this research uses descriptive qualitative research. The results of this study indicate that the coordination is carried out in a bottom-up manner with the initiation of the RT/RW by collecting data on people who have suitable criteria for the beneficiaries of social rehabilitation services for uninhabitable houses in the city of Surabaya.